Group B streptococcal necrotizing pneumonia in a diabetic adult patient - Pacha, Andrea Silvia (2017)
The aim of this report is to describe a rare case of necrotizing pneumonia due to group B Streptococcus serotype III in a relatively young male adult (48 years old) suffering from diabetes. The organism was isolated from his pleural fluid and was only resistant to tetracycline. The patient first received ceftazidime (2 g/8 h i.v.) + clindamycin (300 mg/8 h) for 18 days and then he was discharged home and orally treated with amoxicillin clavulanic acid (1 g/12 h) for 23 days with an uneventful evolution. As in the cases of invasive infection by Streptococcus pyogenes, clindamycin could prevent streptococcal toxic shock syndrome.